Self-assembly of complex hollow CuS nano/micro shell by an electrochemically active bacterium Shewanella oneidensis MR-1. (January 2017) - Xiao, Xiang; Liu, Qiu-Yue; Lu, Xue-Rong; Li, Ting-Ting; Feng, Xiao-Li; Li, Qian; Liu, Zhao-Ying; Feng, Yu-Jie
Abstract: In the present study, Shewanella oneidensis MR-1 was successfully exploited to produce CuS nanocrystals not only as a biotemplate but also as a supplier of sulfur source. The biogenic H2 S produced via the thiosulfate reduction in periplasm grabbed Cu(II) ions bound with extracellular polymeric substance of Shewanella and precipitated as monodisperse CuS nanoparticles extracellularly. These nanoparticles aggregated in the extracellular matrix gradually and then formed CuS nanorods. Ultimately, a complex hollow CuS microshell self-assembled on the cell surface was observed for the first time. The biogenic CuS microshell could significantly enhance the adsorption ability of S. oneidensis MR-1 toward Cr(VI). This work may facilitate a better understanding about the biosynthesis mechanism of nanomaterials and contribute to the application in environmental remediation. Graphical abstract: Highlights: Hollow CuS nano/micro shells were self-assembled by S. oneidensis MR-1. S. oneidensis MR-1 acted as a biotemplate and a sulfur supplier. EPS acted as nucleation site for the biofabrication of CuS nanoparticles. CuS nanorods aggregated to self-assemble a hollow CuS shell extracellularly. CuS shell enhanced the adsorption ability of S. oneidensis MR-1 to Cr (VI).